Blended learning in higher education: an overview / Naemah Abdul Wahab, Jamal Othman and Saiful Nizam Warris - Abdul Wahab, Naemah; Othman, Jamal; Warris, Saiful Nizam (2016)
Blended learning is an innovative approach in creating motivating and meaningful learning experiences to fulfil learner's technological demands in the rapidly changing electronic era. Recognizing the emerging implementation of this learning method, this study explores the definitions, the rationale, past studies, the importance as well as the drawbacks, the issues arising and the suggestions in achieving a successful blended education implementation in higher education settings. From this study, we found that blended environment encourages the foundation of creating independent learners with reasonable critical thinking skills that are valuable for the current working environments. Blended learning is also a solution for classroom insufficiencies as well as teaching and learning flexibility. Nevertheless, not all the courses in higher education settings could apply the blended learning. Therefore, options should be given to the learners by the institution's administrator to either choose a conventional teaching method or a blended course. This alternative will overcome the issues for the low achievers who are unable to survive in blended approach and caters the needs for difficult courses that require a fully face-to-face classroom environment.